Evaluation of morphological varieties of the soft palate on digital cephalograms in 15-35 year-old subjects - Roshanak Ghaffari; Saeed Azarbayejani; Samira-Sadat Nourbakhsh (Isfahan University of Medical Sciences, 2012)
Introduction: The soft palate is the posterior fibro-muscular portion of the palate, with a main role in velopharyngeal closure which assists in the normal functions of sucking, swallowing and pronunciation. The aim of this study was to investigate variations in the morphology of soft palate in normal subjects. Materials and Methods: In this descriptive-analytical study 169 digital lateral cephalograms were selected from normal Iranian subjects (94 women and 75 men), with age ranges of 15-20 and 21-35, referring to a private oral radiology center in Isfahan. Morphology of the soft palate on lateral cephalograms was examined and classified into 6 types. In addition, the soft palate lengths in each type and differences in relation to age and gender were evaluated. Data were analyzed by t-test, chi-squared test and one-way ANOVA (p value > 0.05). Results: The morphology of the soft palate was classified into 6 types. Type 1 (leaf-shaped) was the most prevalent. There was a significant difference in the shape of the soft palate between males and females (p value = 0.02). The mean length of the soft palate in men was more than that in women (p value = 0.03). In addition, the soft palate length in type 3 (butt-like( was significantly shorter than that in other types (p value < 0.05). Conclusion: The soft palate exhibits variable radiographic appearances on lateral cephalograms. Attention to these anatomic variations might assist velopharyngeal closure in patients with cleft palate, obstructive sleep apnea syndrome and speech disorders. Key words: Cephalometry, Digital radiography, Soft palate.